1998
DOI: 10.1292/jvms.60.765
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma LH and Testosterone Levels and Semen Quality after a Single Injection of hCG in Two Dogs with Spermatogenic Dysfunction.

Abstract: ABSTRACT. Plasma LH and testosterone (T) levels and semen quality after a single intramuscular injection of 1,000 IU hCG were investigated in a Beagle dog with azoospermia and a Beagle dog with poor semen quality. The plasma LH levels of both dogs did not change after the treatment. Although the plasma T levels of the dog with azoospermia increased temporarily, no sperm were detected in its semen. In the dog with poor semen quality high levels of plasma T were maintained for 2 weeks after hCG treatment and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…We found that the low-dose hCG therapy administered improved semen quality, as indicated by the total number of sperm in the ejaculate and sperm motility, and produced an increase in plasma T levels in three of the four dogs. The same findings were previously reported for a single high-dose administration of 1000 IU of hCG in dogs with spermatogenic dysfunction (Kawakami et al 1998). These results are consistent with the finding that low-dose hCG therapy substantially restored intratesticular and serum T levels in otherwise healthy men with T-induced negative feedback suppression of gonadotropin (Coviello et al 2005).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found that the low-dose hCG therapy administered improved semen quality, as indicated by the total number of sperm in the ejaculate and sperm motility, and produced an increase in plasma T levels in three of the four dogs. The same findings were previously reported for a single high-dose administration of 1000 IU of hCG in dogs with spermatogenic dysfunction (Kawakami et al 1998). These results are consistent with the finding that low-dose hCG therapy substantially restored intratesticular and serum T levels in otherwise healthy men with T-induced negative feedback suppression of gonadotropin (Coviello et al 2005).…”
Section: Discussionsupporting
confidence: 89%
“…The same findings were previously reported for a single high‐dose administration of 1000 IU of hCG in dogs with spermatogenic dysfunction (Kawakami et al. ). These results are consistent with the finding that low‐dose hCG therapy substantially restored intratesticular and serum T levels in otherwise healthy men with T‐induced negative feedback suppression of gonadotropin (Coviello et al.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although the percentage of sperm with the knobbed acrosome abnormality remained high after the GnRH-A therapy (21% at 14 weeks after the first injection), the bitch gave birth to 5 normal, healthy puppies 61 days after intravaginal artificial insemination. Normal plasma T levels and normal semen quality in adult Beagles have been reported to be as follows (mean ± SE): plasma T level, 2.6 ± 0.7 ng/ml; total semen volume, 13.4 ± 1.4 ml; total number of sperm, 462.5 ± 37.8  10 6 ; percentage of actively motile sperm, 89.4 ± 1.6%; and total percentage of abnormal sperm (mainly tail abnormalities), 9.3 ± 0.8% [5]. Although it has been reported that two of four dogs with knobbed acrosome abnormality had normal fertility [11], the plasma T level and semen quality of the dog in this study was obviously inferior to that of normal dogs.…”
mentioning
confidence: 99%